Vertical protein spot chains – proteomic indicators of proteolysis in dry-cured ham? - Skrlep M.; Candek-Potokar M.; Šegula B.; Chambon C.; Santé-Lhoutellier V. (7th International Symposium on the Mediterranean Pig, 2012)
Proteomic profile of Slovenian "Kraški pršut" dry-cured ham matured for 14 months, was studied. Insoluble protein fraction was extracted from dry-cured Biceps femoris muscles. 2-dimensional SDS PAGE gels (24 samples in three technical repetitions) were made and the protein pattern analysed. Several distinctive protein spot patterns (i.e. protein spot chains containing spots that differed in molecular weight but not in isoelectric point) were observed. The patterns were highly repeatable between the technical repetitions. The subsequent identifications showed the same protein inside one spot chain. Differences in estimated molecular weight between the spots from the same chain indicate the protein degradation, however, it could not be confirmed by the mass spectrometry (lacking accuracy). For firmer confirmation of our hypothesis, a comparison of proteomic profile of hams in different processing phases is needed.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)